2020
DOI: 10.48550/arxiv.2012.08283
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mahler's method in several variables and finite automata

Abstract: We develop a theory of linear Mahler systems in several variables from the perspective of transcendence and algebraic independence, which also includes the possibility of dealing with several systems associated with sufficiently independent matrix transformations. Our main results go far beyond the existing literature, also surpassing those of two unpublished preprints the authors made available on the arXiv in 2018. The main new feature is that they apply now without any restriction on the matrices defining t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
(90 reference statements)
0
1
0
Order By: Relevance
“…Unfortunately, this says nothing about points x for which dim H (O a,x ) = 0, since all such points form a zero dimensional set. Recently, B. Adamczewski and C. Faverjon [1] showed that an irrational number cannot be automatic in bases a and b; being automatic is a computational notion of "simplicity", and so this can be seen as a first verification that an irrational number cannot be "too simple" in two multiplicatively independent bases.…”
Section: Furstenberg's Sumset Slice and Orbit Conjecturesmentioning
confidence: 99%
“…Unfortunately, this says nothing about points x for which dim H (O a,x ) = 0, since all such points form a zero dimensional set. Recently, B. Adamczewski and C. Faverjon [1] showed that an irrational number cannot be automatic in bases a and b; being automatic is a computational notion of "simplicity", and so this can be seen as a first verification that an irrational number cannot be "too simple" in two multiplicatively independent bases.…”
Section: Furstenberg's Sumset Slice and Orbit Conjecturesmentioning
confidence: 99%